ZPD-2, a Small Compound That Inhibits α-Synuclein Amyloid Aggregation and Its Seeded Polymerization - Peña-Díaz, Samuel; Pujols, Jordi; Conde-Giménez, María; Čarija, Anita; Dalfo, Esther; García, Jesús; Navarro, Susanna; Pinheiro, Francisca; Santos, Jaime; Salvatella, Xavier; Sancho, Javier; Ventura, Salvador (Frontiers in Molecular Neuroscience, 2019)
α-synuclein forms toxic intracellular protein inclusions and transmissible amyloid structures in Parkinson’s disease. Preventing α-synuclein self-assembly has become one of the most promising approaches in the search for disease-modifying treatments for this neurodegenerative disorder. Here, we describe the capacity of a small molecule (ZPD-2), identified after a high-throughput screening, to inhibit α-synuclein aggregation. ZPD-2 inhibits the aggregation of wild-type α-synuclein and the A30P and H50Q familial variants in vitro at substoichiometric compound:protein ratios. In addition, the molecule prevents the spreading of α-synuclein seeds in protein misfolding cyclic amplification assays. ZPD-2 is active against different α-synuclein strains and blocks their seeded polymerization. Treating with ZPD-2 two different Parkinson’s Disease Caenorhabditis elegans models which express α-synuclein either in muscle or in dopaminergic neurons substantially reduces the number of α-synuclein inclusions and decreases synuclein-induced dopaminergic neurons degeneration. Overall, ZPD-2 is a hit compound worth to be explored in order to develop lead molecules for therapeutic intervention in Parkinson’s Disease.